Glycans in Infectious Diseases. A Molecular Recognition Perspective - Unione, Luca; Gimeno, Ana; Valverde, Pablo; Calloni, Ilaria; Coelho, Helena; Mirabella, Stefania; Poveda, Ana; Arda, Ana; Jimenez-Barbero, Jesus (Current Medicinal Chemistry, 2017)
Background: From the simplest bacteria to the highest complex mammals, including humans, every single cell is covered by a dense coat of glycans. Glycans are involved in almost every biological process that takes place in our body, playing a central role in the communication between cells and their environment. Glycans are also involved in infectious diseases, which arise from the specific interaction between glycans of the pathogen cell coat and specific receptors on the host cell or vice versa. Objective: The understanding of the mechanisms governing these specific carbohydrateprotein interactions, at atomic and molecular levels, is crucial to develop new drugs able to block the infection and to avoid the disease. Methods: Recent advances in biophysical techniques allow for a complete picture of the hostpathogen infection event, unveiling the key aspects of the molecular interaction and, thus, providing an opportunity to interfere with it. Conclusion: In this general review, we discuss some recent contributions, providing a summary of what we consider the most innovative and inspiring research lines to the field.
Keywords: Glycans